Construction of a short metallofullerene-peapod with a spin probe. Issue 77 (6th September 2019) - Zhao, Chong; Meng, Haibing; Nie, Mingzhe; Huang, Qiang; Du, Pingwu; Wang, Chunru; Wang, Taishan
Abstract : A short metallofullerene-peapod of Y2 @C79 N⊂[4]CHBC was constructed with a distinct structure and typical spin character. Abstract : A short metallofullere-peapod of Y2 @C79 N⊂[4]CHBC was constructed. The strong confinement effect from the large π-extended [4]CHBC nanoring induces molecular orientation of the wrapped Y2 @C79 N, which can be sensed by a Y2 @C79 N spin probe. The low susceptibility of the spin phase memory time ( T m ) for the Y2 @C79 N spin was also found in a confined space.